A decade of hospital-based violence intervention: Benefits and shortcomings. Issue 6 (December 2016) - Juillard, Catherine; Cooperman, Laya; Allen, Isabel; Pirracchio, Romain; Henderson, Terrell; Marquez, Ruben; Orellana, Julia; Texada, Michael; Dicker, Rochelle Ami
Abstract : INTRODUCTION: Initial analyses of hospital-based violence intervention programs (VIPs) have demonstrated decreased violent injury recidivism. Long-term VIP performance has not been assessed. Violence intervention program quality improvement requires evaluation to identify shortcomings and client subpopulations warranting additional resources. We evaluated our case manager–based VIPs to identify modifiable risk factors that most impact violent injury recidivism and determine subpopulations that need modification of targeted services. METHODS: Data on demographic variables, socioeconomic factors, needs, and injury recidivism from 2005 to 2014 were collected through our VIP database. Possible client needs included housing, education, employment, court advocacy, driver's license obtainment, and "other." Case managers assessed needs as "not needed, " "identified (unmet), " and "met." χ 2 And nonparametric tests were used to identify factors associated with recidivism reduction. RESULTS: Over the 10-year period, 466 clients were enrolled in VIP. During the program period, the violent reinjury rate was 4%, as compared with a historical control of 8% from 2000 to 2004. Women had lower rates of reinjury than men (3% vs 13%, respectively, p = 0.023). Blacks had the lowest recidivism (2%, p < 0.0001), whereas a higher rate (11%) was observed among Latinos. Although a minority of clients (5%), 100% of white clients were reinjured. Mental health services (51%), victim-of-crime compensation (48%), employment (36%), and housing (30%) were the most frequently identified needs. Expressing the need for education was significantly associated with likelihood of reinjury, an effect that was completely reversed when the need was met. CONCLUSION: This evaluation of a VIP demonstrates sustained recidivism reduction and success in addressing client needs from a traditionally underserved population. Efforts to identify and address root causes of Latino and white client reinjury should be increased. Violence intervention program prioritization of housing needs may reduce future reinjury. This study demonstrating sustainable success underscores the importance of increased integration of VIP into trauma centers nationally. LEVEL OF EVIDENCE: Therapeutic study, level III.